Hubungan Kadar Hemoglobin Terhadap Status Gizi Pelajar Di Mi Muhammadiyah Program Khusus Kartasura - Alhaq, Nafi'udin, dr. Anika Candrasari, M.Kes, dr. Mohammad Shoim Dasuki, M. Kes (2015)
Background: Based on the IPM report, Indonesia ranks 108 out of 177 countries in the world. The sequence is under five ASEAN countries such as Singapore (9), Brunei Darussalam(30), Malaysia (62). According Riskesdas, Central Java province is includes in the 15 provinces with the prevalence of thinness in children 6-12 years above the national prevalence and entered into 11 provinces who had obesity prevalence above national prevalence. Based on the above, the authors is interested to raise the topic of research on the relationship between hemoglobin levels on the nutritional status of students in MI Muhammadiyah Special Programs Kartasura. Method: The method uses analytic observational, cross-sectional approach. The number of research respondents were 48. The sampling technique by simple random sampling. Measurement of hemoglobin levels with sianmethemoglobin, while the measurement of nutritional status with Z score value. Data were analyzed by Chi-square test. Result: The research result showed that the p value = 0,205 (p > 0,05) showed that there was no relationship between hemoglobin levels on the nutritional status of students. Conclusion: There is no relationship between hemoglobin levels on the nutritional status of students in MI Muhammadiyah Special Programs Kartasura.